PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIPLE INTELEGENCES DI PONDOK PESANTREN SMP AL-FALAH TERPADU - Mahrina Mahrina (CV. ADIBA ASIHA AMIRA, 2023)
Every Human being is ekuipped with various competencies and talents and intelligences,of cours if thise various intelligences are explored continuously in the right way then human beings will emerge who have superior competence in their respective fields. In this study using a kualitative approach by discovering new theories af research conceptsin addition to the development of knowledge with in educational institution under study. Integrated Al-falah Middle School Islamic Boarding school using Multiple Intelligences Islamic Religion Education Learning strategies which assume that intelligence is multiple,not only in one area of intelligence. The first time student enter their school they are observed by the teachers to find out their intelligence potential, then the teacher can determine the learning strategy to be used. The next expected result is that students cat get learning according to their talents and skills so that they enjoy each subject matter comfortably so that learning material is more easily accepted by students with a more focused focus.